2013
DOI: 10.1111/ctr.12198
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in kidney transplant patients with diabetes

Abstract: Among kidney transplant patients between the ages of 18-74, non-diabetics have significantly higher HRQOL scores on the EQ-5D, HUI-III, and SF-6D compared with patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…402 This is a recent study 402 in the relevant patient population and reports EQ-5D utility data, with an estimated disutility of 0.06 associated with NODAT. This figure does not adjust for people with CVD complications and therefore is appropriate to how we model NODAT.…”
Section: Disutility Due To Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…402 This is a recent study 402 in the relevant patient population and reports EQ-5D utility data, with an estimated disutility of 0.06 associated with NODAT. This figure does not adjust for people with CVD complications and therefore is appropriate to how we model NODAT.…”
Section: Disutility Due To Diabetes Mellitusmentioning
confidence: 99%
“…This figure does not adjust for people with CVD complications and therefore is appropriate to how we model NODAT. We note that the study 402 was conducted in only one hospital in USA and the valuation set for the utility values is US based, 403 so the outcomes may not be generalisable to the UK population. It has been demonstrated by Johnson et al 404 that US-valued health states are statistically higher than the UK-valued health states for 31 out of 42 valued EQ-5D health states and that extreme health states are most notably different.…”
Section: Disutility Due To Diabetes Mellitusmentioning
confidence: 99%
“…Some of the items may be irrelevant to measure QoL after transplantation and may neglect other issues likely to be important . Several other generic instruments have been used to evaluate QoL in transplanted patients, namely the Karnofsky Index and the EuroQol‐5 Dimensions (EQ‐5D) . Disease‐specific surveys have been developed to measure changes in particular diseases, mostly after a treatment.…”
mentioning
confidence: 99%
“…We asked each patient who consented to participate in this study, the changes felt from pre‐transplantation to the present, after transplantation. The EQ‐5D‐5L has already been validated for Portuguese population and in renal transplants without or with diabetes . The GIQLI has also been used and validated in renal transplants for the Spanish population .…”
mentioning
confidence: 99%
“…(17) One single-institution study found that non-diabetics had a significantly higher health-related quality of life following renal transplantation. (18) Given that co-morbid diabetes is lower among older recipients, it is possible that this finding may be generalizable to a large number of this population. Our findings may also aid in educating older recipients regarding the relative hazards associated with the transplantation of select donor organs of lesser quality.…”
Section: Discussionmentioning
confidence: 87%